Predictive Ability of Procalcitonin (PCT) as a Predictor for Acute Pyelonephrtitis (APN) and Late Renal Scars (RS) in Children with UTI: Meta-Analysis on Individual Patient Data - Leroy, S.; Fernandez, A.; Nifkar, R.; Romanello, C.; Bouissou, F.; Gervaix, A.; Chalumeau, M. (Springer, 2010)
[Abstract Not Available]